Is Multi-Level Governance a Political Choice or a Service Delivery Necessity? - Kakubava, Nino (Caucasus Journal of Social Sciences, 2013)
The notion of multi-level governance first appeared with the estab-lishment of the European Union to describe the transfer of power upwards and downwards. Later, the power transfer appeared not only vertically, but also horizontally by involving non-gover-nmental, voluntary and private sector into public policy making. Apparently, traditional model of policy making has been chal-lenged and replaced by a more complex, decentralized structure, better able to accommodate citizens’ needs at various levels. How-ever, whether states transfer authority for the purpose of better service delivery or whether they do it under pressure is still un-clear. This paper aims at answering this question by examining various types of multi-level governance and analyzing recent de-velopments in the UK policy as a case.